Velocity Structure Correlations between the Nebular, Molecular, and Atmospheric Gases in the Cores of Four Cool Core Clusters - Muzi Li; B.R. McNamara; Alison L. Coil; Marie-Joëlle Gingras; Fabrizio Brighenti; H.R. Russell; Prathamesh D. Tamhaneh; S. Peng Oh; Serena Perrotta (The Astrophysical Journal)
We investigate the velocity structure of nebular gas in the central galaxies of four clusters: A1835, PKS 0745−191, A262, and RXJ0820.9+0752, using data from the Keck Cosmic Web Imager. Velocity structure functions (VSFs) of the [O ii ] emission line are compared to VSFs of molecular clouds observed with the Atacama Large Millimeter/submillimeter Array. Apart from A262, where the gas is located in a circumnuclear disk, the nebular gas in the remaining galaxies lies in off-nuclear filamentary structures with VSFs steeper than the Kolmogorov slope. This steepening may be plausibly attributed to gravity, although other factors, such as magnetic stresses and bulk motion, may be significant. The VSFs of CO and [O ii ] emission are similar in RXJ0820 and A262, indicating close coupling of the nebular and molecular gases. In contrast, the nebular and molecular gases are differentiated on most scales in PKS 0745 and A1835. This discrepancy is likely due to the radioactive galactic nucleus churning the gas. We compare the scale-dependent velocity amplitudes of the hot atmospheres constrained by X-ray surface brightness fluctuation analysis using Chandra observations to the nebular VSFs. The large-scale consistency in A1835 and RXJ0820 is consistent with condensation from the hot atmospheres. We explore substantial systematic biases, including projection effects, windowing, and smoothing effects, when comparing VSFs using different telescopes and instruments.